Adopting restriction: how coalition governments respond to radical right parties - Fabio Ellger; Heike Klüver (West European Politics, 2024)
Radical right parties (RRPs) have gained representation in parliaments across Europe, but little is known about their impact on government policy. Even though RRPs tend to end up in opposition, they have considerable influence on policy making within coalition governments. One expectation is that coalition governments are tough on immigration to optimise voter support when being exposed to right-wing parties in parliament. Coalition negotiations temporarily reduce accountability and allow cabinets to adjust policy positions without bearing the costs associated with opportunistic behaviour. This argument is tested using novel data on pre-electoral policy positions and post-electoral immigration policies for coalition cabinets in 24 European democracies from 1980 to 2015. The findings reveal that governments shift to more restrictive immigration policies in face of RRPs. This article expands on prior research on the influence of the radical right by demonstrating its direct influence on coalition governments' joint immigration policy plans.
https://doi.org/10.7910/DVN/SW0WEG
Keywords: 320; Comparative politics; coalition government; radical right parties; immigration policy